Wanda Koop : see Everything / See Nothing - Laurence, Robin (CV Photo, 2000)
Summary Best known as a painter, Wanda Koop is also a gifted videographer who produces scrolls of video stills as well as large-scale installations combining video projections and painting. Many of her images, such as those in See Everything/See Nothing, originate in travel, and reflect on belonging and alienation, familiarity and strangeness, home and away.